Global Liquidity and Financial Stress: Evidence from Major Emerging Economies. Issue 12 (1st December 2016) - Cevik, Emrah I.; Kirci-Cevik, Nuket; Dibooglu, Sel
ABSTRACT: We examine the relationship between financial stress and global liquidity for the so-called fragile five emerging economies (Brazil, India, Indonesia, South Africa, and Turkey). By using an extensive set of variables that take into account the structural characteristics of these economies, we construct a financial stress index. We then use a Markov regime switching model to identify the high financial stress episodes. We examine periods of heightened financial stress and its relationship to high incidence of domestic and global disturbances. Finally, we construct a global financial liquidity index and assess the relationship between financial stress and global liquidity. Using a bivariate Markov regime switching VAR model, we find a regime-dependent relation between global liquidity and financial stress. Moreover, global liquidity shocks seem to strain these emerging economies in such a way that global illiquidity heightens financial stress.